2013
DOI: 10.1057/jit.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ICT-Enabled Product and Process Innovations at the Bottom of the Pyramid: A Market Separations Perspective

Abstract: Innovations in products and processes enabled by ICT such as mobile phones and the Internet constitute a rapidly emerging means of market development at the Bottom of the Pyramid (BOP), which consists of people who earn less than US$2 a day. However, these ICT-enabled market development efforts have not always yielded positive developmental outcomes, in part because market development is hindered by remote location and geographic dispersion of BOP communities, their low and uncertain incomes, and informal loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Due to the lack of a reliable networks of electricity, road, technology, information, and transportation across rural areas, they cannot directly access relatively more mainstream buyers and social interest groups, and are unfortunately deprived of their earnings by intermediaries. As a result, their income generation prospects are limited [54]. Once joining the RDCBM innovation, farmers pay considerably more attention to the realization of self-interest.…”
Section: Rural Needs Identifyingmentioning
confidence: 99%
“…Due to the lack of a reliable networks of electricity, road, technology, information, and transportation across rural areas, they cannot directly access relatively more mainstream buyers and social interest groups, and are unfortunately deprived of their earnings by intermediaries. As a result, their income generation prospects are limited [54]. Once joining the RDCBM innovation, farmers pay considerably more attention to the realization of self-interest.…”
Section: Rural Needs Identifyingmentioning
confidence: 99%
“…• rodrigo luiz morais da silva • adriana roseli wünsch takahashi • andrea paula segatto • markets, as the products or services offered mainly in order to mitigate some social problems related to poverty can be re-adequate (Karippacheril, De Reuver, & Bouwman, 2013), innovated radically or incrementally (Tarafdar, Singh, & Anekal, 2013) and even disruptively (Hart & Christensen, 2002;Nakata & Weidner, 2012). Previous experience with the business or the SI was another element identified as relevant because, according to Le Ber and Branzei (2010a) and Bhatt and Altinay (2013), the experience of the organization and its members is an important ally in step growth of a SI.…”
Section: Selected Articles For Meta-synthesismentioning
confidence: 99%
“…All the market separations are generally high at BOP (Tarafdar et al 2013). Spatial separations exist due to remote location of most BOP communities, which are situated in physically inaccessible places with lesser accessibility (Vachani and Smith 2008).…”
Section: Market Separations At Bopmentioning
confidence: 99%
“…This segment of population has unique needs, constraints, and challenges and majority of them live outside the confines of the formal economy (London 2008). Recent studies (e.g., Tarafdar et al 2013) have shown that BOP is largely an outcome of market separations. Bartels (1968) posited a general sub-theory of economic (market) separations which suggests that consumers are separated from producers due to geographic, economic, temporal, and informational separations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation